The Transformative Strategic Program of the Men's Health and Reproductive Health Research Center: A Letter to the Editor-in-Chief - Emami, Hassan (Archives of Men's Health, 2024)
The Men's Health and Reproductive Health Research Center is addressing a critical challenge: the health needs of a vital segment of society that is often overlooked. Men, who represent half of the population, play an essential role in family and societal security. Their health is intrinsically linked to economic, social, cultural, and overall health development. Research reveals a concerning trend: men are generally less healthy than women, engage in riskier lifestyles, and exhibit lower levels of health awareness (1). They are more susceptible to various health risk factors, highlighting the urgent need for targeted interventions to enhance their well-being. Increasing health awareness through planning, training, and education is paramount. Furthermore, the prevalence of primary infertility in Iran stands at 18.3%, with 32% of cases attributed to unexplained causes, 12.5% to female causes, and 13.6% to male causes. As in many countries, infertility presents significant psychological and social challenges for Iranian couples (3). The issue of infertility affects millions of couples in Iran (4), carrying substantial implications for both individual and societal well-being. Comprehensive healthcare services for this demographic are crucial, especially considering population policies aimed at fostering healthy families.